Land Ownership Rights to Cultural Reserve Buildings in Surabaya based on Basic Agrarian Law and Cultural Heritage Law - Arin Tri Arbawati; Astrid Athina Indradewi (Activa Yuris: Jurnal Hukum, 2024)
In colonial times, the city of Surabaya was an important part that held a lot of history. Surabaya is known as the oldest port city in Indonesia during the Dutch East Indies era and was the centre of government and international trade. Apart from that, Surabaya was also named a city of heroes because the heroes at that time were willing to sacrifice themselves to fight for and defend the independence of the Republic of Indonesia by fighting the invaders. On that basis, Surabaya is rich in cultural heritage. Most of the heritage of these historic buildings is still standing and can be found in several areas of the city of Surabaya. The local Department of Tourism and Culture has established regulations to protect original historic buildings as city heritage. However, in fulfilling the rights and obligations of individuals and city governments, land rights owned from generation to generation must be considered by the local city government. This research uses normative juridical with doctrinal and statutory regulatory approaches. This research aims to find regional regulations regarding cultural heritage related to ownership rights in managing cultural heritage land and buildings.